Evaluation of the potential drug interactions mediated through P‐gp, OCT2, and MATE1/2K with filgotinib in healthy subjects. Issue 2 (25th September 2021) - Hsueh, Chia‐Hsiang; Anderson, Kacey; Shen, Gong; Yun, Chohee; Qin, Ann; Othman, Ahmed A.
Abstract: Filgotinib, a preferential Janus Kinase‐1 inhibitor, is approved in Europe and Japan for treatment of rheumatoid arthritis and is being developed for treatment of other chronic inflammatory diseases. Three drug‐drug interactions studies were conducted in healthy subjects to evaluate the effect of P‐glycoprotein (P‐gp) modulation (study 1: P‐gp inhibition by itraconazole and study 2: P‐gp induction by rifampin) on filgotinib pharmacokinetics and the potential of filgotinib to impact exposure of metformin, an organic cation transporter (OCT) 2 and multidrug and toxin extrusion (MATE) 1/2K substrate (study 3). Co‐administration of filgotinib with itraconazole increased filgotinib exposure (maximum concentration [ C max ] by 64% and area under the curve to infinity [AUCinf ] by 45%) but had no effect on the exposure of GS‐829845, filgotinib's primary metabolite. Rifampin moderately reduced exposures of filgotinib and GS‐829845 ( C max by 26% and AUCinf by 27% for filgotinib; C max by 19% and AUCinf by 38% for GS‐829845). The data confirmed that filgotinib is a P‐gp substrate. However, the magnitude of change in filgotinib/GS‐829845 exposure by P‐gp modulators is not deemed to be clinically relevant based on filgotinib exposure‐response analyses in subjects with rheumatoid arthritis. Filgotinib did not alter metformin exposures, indicating that filgotinib and GS‐829845 do not inhibit OCT2 and MATE1/2K at the clinical doses. Filgotinib was generally well‐tolerated when administered alone or with the co‐administered drugs in the studies. Results from these studies were the basis to enable the use of P‐gp modulators and substrates of OCT2, MATE1, and MATE2K with filgotinib without the need for dose modifications in the current approved rheumatoid arthritis population.